Influence of essential oils in diet and life-stage on gut microbiota and fillet quality of rainbow trout (Oncorhynchus mykiss). (3rd April 2018) - Ceppa, Florencia; Faccenda, Filippo; De Filippo, Carlotta; Albanese, Davide; Pindo, Massimo; Martelli, Roberta; Marconi, Paola; Lunelli, Fernando; Fava, Francesca; Parisi, Giuliana
Abstract: Developing fish farming to meet the demands of food security and sustainability in the 21st century will require new farming systems and improved feeds. Diet and microbe interactions in the gut is an important variable with the potential to make a significant impact on future fish farming diets and production systems. It was monitored the gut microbiota of farmed rainbow trout using 16S rRNA profiling over 51 weeks during standard rearing conditions and feeding diet with supplementation of an essential oils (MixOil) mixture from plants (at a concentration in diet of 200 mg/kg). Gut microbiota 16S rRNA profiling indicated that the fish gut was dominated by Actinobacteria, Proteobacteria, Bacteroidetes and Firmicutes. Although the dietary supplementation with MixOil had no impact on either the composition or architecture of gut microbiota, significant changes in alpha and beta diversity and relative abundance of groups of gut bacteria were evident during growth stages on test feeds, especially upon prolonged growth on finishing feed. Fish fillet quality to guarantee palatability and safety for human consumption was also evaluated. Significant differences within the gut microbiota of juvenile and adult trout under the same rearing conditions were observed, The addition of essential oil blend affected some physicochemical characteristics of trout fillets, including their resistance to oxidative damage and their weight loss (as liquid loss and water holding capacity) during the first period of storage, that are two important parameters related to product shelf life and susceptibility to spoilage. The results highlighted the need for further studies concern dietary microbiome modulation at different life stages and its influence on animal health, growth performance and final product quality.